Clinical Features of Neuroendocrine Carcinoma of the Uterine Cervix. Issue 7 (September 2015) - Nagao, Shoji; Miwa, Maiko; Maeda, Naoko; Kogiku, Ai; Yamamoto, Kasumi; Morimoto, Akemi; Wakahashi, Senn; Ichida, Kotaro; Sudo, Tamotsu; Yamaguchi, Satoshi; Sakuma, Toshiko; Fujiwara, Kiyoshi
<x xml:space="preserve">Abstract</x> Objective Neuroendocrine carcinoma of the cervix is a rare and aggressive subtype of cervical cancer and includes small cell neuroendocrine carcinoma (SCNEC) and large cell neuroendocrine carcinoma (LCNEC). We conducted a single-institution retrospective review to explore the pattern of treatments and outcomes with the aim of defining an optimum treatment strategy for these carcinomas. Methods Twenty-three consecutive patients with SCNEC or LCNEC of the cervix diagnosed at the Hyogo Cancer Center between 1996 and 2013 were included in this study. Pertinent information, including clinical and pathological characteristics, and survival data were collected from clinical records and/or telephone surveys. The pathological review was conducted by a pathologist specializing in gynecologic cancer. Results Eleven patients had SCNEC and 12 had LCNEC. Eighteen patients with International Federation of Gynecology and Obstetrics (FIGO) stage I/II underwent type III radical hysterectomy with pelvic lymphadenectomy. After surgery, 9 received adjuvant chemotherapy (8, irinotecan plus cisplatin; 1, paclitaxel plus carboplatin), 7 received concurrent chemoradiation therapy (CCRT; 6, nedaplatin; 1, cisplatin), and 2 received radiation therapy (RT). Patients who received adjuvant chemotherapy had a better overall survival than did patients who received CCRT or RT (hazard ratio, 0.21; 95% confidence interval, 0.030–1.51; P = 0.12). Although the overall survival rates are not statistically significant, the 9 patients who underwent radical hysterectomy followed by adjuvant chemotherapy are all alive. Among the remaining 5 patients who did not undergo radical hysterectomy, 2 with FIGO stage III and 1 with stage IVa received CCRT, and 2 with stage IVb received palliative RT or chemotherapy. These 5 patients with FIGO stage III/IV died of disease within 36 months. Conclusions Radical hysterectomy followed by platinum-based chemotherapy, especially the irinotecan plus cisplatin combination, is beneficial for long-term survival in patients with early-stage neuroendocrine carcinoma of the cervix.